King of thorns eaudiobook Broken empire series, book 2. - Lawrence, Mark (The Broken Empire, 2012)
The follow-up to Mark Lawrence's thrilling debut novel Prince of Thorns, King of Thorns continues the tale of antihero Jorg Ancrath. After wresting back control of his kingdom from those who murdered his family, Jorg sees the land erupt with hundreds of battles fought by lords and petty kings. More daunting still, he faces an enemy many times his own strength. Jorg may not be able to win this battle in a fair fight, but he wields a rage and cunning that just might even the odds.